EXPERT ASSESSMENT OF THE PROFESSIONAL COMPETENCIES OF THE RESCUERS - Hakobyan, Karine; Stepanyan, Lusine (Modern Psychology, 2024)
The professional work of rescuers is of crucial importance in emergency situations, where the efficiency of rescue operations and the safety of both rescuers and victims directly depend on their professional competences.The purpose of this investigation is to study the key professional qualities and skills that are necessary for the effective professional activity of rescuers.28 experienced rescuers with 10 or more years of professional experience took part in the research. The expert survey method was used to study important professional qualities of rescuers. This method was applied using a questionnaire method.15 specific skills and qualities were extracted, which were gathered in groups of professional abilities, personal traits and social skills.According to the results, the most important characteristics for a successful rescue operation is a low level of anxiety, team leadership and management skills, physical training and endurance. The study also revealed personal qualities and social skills of rescuers’ profession, showing the importance of effective communication, leadership and teamwork.These results point out the issue of technical competencies giving priority to the development of personal and social skills at the same time. While hard skills can be acquired through training, the development of social skills and improvement of certain personal traits requires constant effort. Focusing on the development of interpersonal relationship, teamwork and stress management, organizations can improve the professionalism and effectiveness of their rescue teams.